Students’ awareness of the bruxism causes, effects and therapies - Mateusz Gizler; Natalia Pietrzak; Klara Saczuk; Monika Lukomska-Szymanska; Barbara Lapinska (Heliyon, 2024)
Objectives: Bruxism is a repetitive activity of the masticatory muscles characterized by clenching or grinding teeth and/or mandibular stiffening. Bruxism manifests itself in two forms: during sleeping and waking. The etiology of bruxism is multifactorial. The treatment of bruxism is mainly based on making the patient aware of the presence of the condition. The aim of the study was to assess knowledge on the causes and the effects of bruxism among Polish students as well as the possible management. Materials and methods: The anonymous online survey was conducted among students (aged between 18 and 25 years old) of universities across Poland, using the Google Forms platform. The survey contained questions concerning bruxism causes, effects and therapies. All variants of answers in these questions contained true information about bruxism. Results: The study found significant differences in awareness of bruxism among genders in favor of females. The awareness of bruxism among population residing in cities and in villages was comparable (p > 0.05). However, the results should be taken with care due to limited number of students that participated in the study and uneven gender distribution among urban and village residents. Conclusions: Within the limitations of the study it can be concluded that the knowledge of bruxism among Polish students is higher in comparison with the findings from the literature, as well as the superiority of women's awareness of bruxism over men. Future studies should be conducted on greater student population, with even distribution of participants among country areas and variety of universities. Significance: The findings may indicate the need for further education of male young adults, on bruxism causes, possible effects and therapies to increase their awareness of bruxism and encourage early diagnosis and treatment.